Kontribusi Pajak Restoran dalam Meningkatkan Pendapatan Asli Daerah Kota Serang - Aprio Gunawan; Refi Pratiwi; Mulyanah Mulyanah; Selly Anggraeni Haryono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The culinary industry in Serang City continues to grow along with the increasing number of restaurants, cafes, and digital-based food service business, making Restaurant Tax one pf the potential sources of Local Own-Source Revenue (PAD) in Serang City. This study aims to determine the entent of the contribution of Restaurant Tax in increasing Local Own-Source Revenue (PAD) in Serang City. The research method used is descriptive analysis. The data used in this study were obtained from the Regional Revenue Agency of Banten Province for the period 2022–2024. The results of the study indicate that the contribution of Restaurant Tax to Local Own-Source Revenue (PAD) in Serang City increased during the period 2022–2024, with contribution percentages of 10.85% in 2022, 12.19% in 2023, and 13.29% in 2024. Although the contribution showed an increasing trend, the percentage remained below 20%, indicating that the contribution level is still categorized as low. This condition is caused by relatively low taxpayer compliance, suboptimal turnover reporting, and limited supervision, particularly for digital-based culinary businesses. Therefore, strategies are needed to optimize Restaurant Tax revenue through strengthening supervision, improving digital-based administrative systems, and enhancing taxpayer compliance through continuous socialization and education programs.